Extreme Contrast Ratio Imaging of Sirius with a Charge Injection Device. (18th January 2016) - Batcheldor, D.; Foadi, R.; Bahr, C.; Jenne, J.; Ninkov, Z.; Bhaskaran, S.; Chapman, T.
Abstract: The next fundamental steps forward in understanding our place in the universe could be a result of advances in extreme contrast ratio (ECR) imaging and point-spread function (PSF) suppression. For example, blinded by quasar light we have yet to fully understand the processes of galaxy and star formation and evolution, and there is an ongoing race to obtain a direct image of an exo-Earth lost in the glare of its host star. To fully explore the features of these systems, we must perform observations in which contrast ratios (CRs) of at least one billion can be regularly achieved with sub 0.″1 inner working angles. Here, we present the details of a latest-generation 32-bit charge injection device (CID) that could conceivably achieve CRs on the order of one billion. We also demonstrate some of its ECR imaging abilities for astronomical imaging. At a separation of two arcminutes, we report a direct CR of, or 1 part in 20 million, from observations of the Sirius field. The atmospheric conditions present during the collection of this data prevented less modest results, and we expect to be able to achieve higher CRs, with improved inner working angles, simply by operating a CID at a world-class observing site. However, CIDs do not directly provide any PSF suppression. Therefore, combining CID imaging with a simple PSF suppression technique like angular differential imaging could provide a cheap and easy alternative to the complex ECR techniques currently being employed.